Phenotypic, pathogenic, molecular and phylogenetic comparisons of bacteria causing Aloe rot from three countries - KUNAL MANDAL* AND N.A. GAJBHIYE, YOGESHWAR KUMAR, JATINDRA NATH SAMANTA (Indian Phytopathology, 2012)
Bacterial soft rot disease of Aloe caused by heterogeneous genus Erwinia was reported from different parts of the world. In the recent past the genus underwent major taxonomic modifications. In the present study, four Aloe pathogenic bacterial strains isolated from India, The Netherlands and Yugoslavia have been compared. Different cultural, biochemical, physiological and pathological characters and protein/lipid profiles indicated that the strains belonged to two different genera, Pectobacterium and Dickeya. Species specific amplification of pel gene sequences also supported this. Phylogenetic analysis of rRNA gene (rDNA) sequence placed these Dickeya strains close to D. dieffenbachiae and D. zeae. On the other hand, phenotypic tests suggested these to be either of D. dadanti, D. dieffenbachiae and D. zeae. On the basis of pathogenicity of the test strains on Dieffenbachia leaves, these were placed in D. dieffenbachiae. The Yugoslavian strain was identified as P. carotovorum. Phenotypic tests, RFLP analyses deciphered variation among the same species. However, none of the six Aloe species tested in the study showed resistance against any of the evaluated bacterial strains.